Analysis of Factors Influencing Financial Literacy in Gen Z - Sholahuddin; Martha Wulandari; Dewi Sartika; Sulaiman Helmi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the factors influencing financial literacy among Gen Z in the city of Palembang. This research employs a quantitative method with SEM-Smart-PLS analysis techniques involving 500 Gen Z respondents in the city of Palembang. Based on the analysis results, financial attitude significantly affects financial literacy, financial behavior significantly affects financial literacy, financial knowledge significantly affects financial attitude, financial knowledge significantly affects behavior, financial knowledge affects financial literacy, financial knowledge and financial attitude significantly affect financial literacy, and financial knowledge and financial behavior significantly affect financial literacy.